Die Einheit des physikalischen Weltbildes. Einsteins Arbeiten zur einheitlichen geometrischen Feldtheorie - Von Borzeszkowski, Horst-Heino (Revista de Filosofía, 2005)
Modern physics is inconceivable without Albert Einstein’s work. His most essential achievements embrace the foundation of the theories of special and general relativity, his contribution to the foundation of quantum theory, and the work done in elaborating these theories. But his genuine intention was much more ambitious. He intended to establish a unified physical theory which was not only to represent some relation between the laws of classical field theory and the rules of quantum physics, but a generalization of his theory of general relativity. For, in comparison with the previous physics, the latter had caused an epochal change of the relation between geometry and physics. According to Einstein’s program of a unified theory, all physical fields and particles were to derive as configurations of a unified geometric field that determines the structure of the space-time. Lmitations and perspectives of this program are discussed.